Infectious endocarditis evolution and lethality in patients attended at Dos de Mayo National Hospital - Sánchez, Evelyn (2006)
Objective: To evaluate infectious endocarditis evolution and lethality as well as complications and their influence on mortality. Design: Non-concurrent longitudinal study. Setting: Dos de Mayo Hospital Cardiology service, a teaching hospital. Patients: Patients with infectious endocarditis. Interventions: Clinical charts, laboratory and echocardiographic (Dukes criteria) studies of patients with infectious endocarditis attended between June 1999 and June 2005 were reviewed. Fisher and Sudent t tests were used for statistical analysis and Kaplan Meier curves comparison and logarithmic range test to evaluate survival. Main outcome measures: Infectious endocarditis complications and mortality. Results: Seventy-five patients were studied, mean age 42,1±20,4 years, 66,7% males; 93,3% presented cardiopathy. Clinical presentation included heart failure (73,3%), encephalopathy (17,3%), and embolic phenomena (50,6%). Laboratory evolution showed worsening renal function. Echocardiography demonstrated presence of vegetations in 97,3% and complications like valve breakage (8%), valve abscesses (4%); 14,7% of patients had surgery. Mortality was 14,7%, caused by renal and septic complications affecting patients' survival. Conclusions: Mortality in this group was 14,7%. Survival was affected by the number of complications, mainly renal and septic complications